Commentary and authority in Mesopotamia and Qumran - Brown-deVost, Bronson; Brandeis University; Vandenhoeck & Ruprecht (Gottingen Vandenhoeck & Ruprecht, 2019)
Intro -- Commentary and Authority in Mesopotamia and Qumran -- Copyright -- Table of Contents -- Acknowledgements -- Introduction -- Preliminaries -- Selection of Corpus -- Enūma eliš Commentary I -- Ludlul bēl nēmeqi -- The Babylonian Theodicy -- Maqlû, Šurpu, and Tummu bītu -- Special Conventions -- Technical Terms -- Transliteration Conventions -- Qumran Texts -- Sigla -- Mesopotamian Texts -- Transliterations and Translations -- A Note on Working with Manuscripts -- Abbreviations and Citations -- Qumran Commentaries: A General Description -- Pesher as Genre -- Selection of Texts -- Dating and Palaeography of Manuscripts -- The Jewish Backgrounds of Qumran Commentary -- Glosses -- Commentary Type Activity -- Implications for Qumran Commentaries -- Qumran Commentaries: A Formal Description -- Physical Layout and Paratextual Features -- Statistical Analysis -- Literary Structural Analysis -- Short Lemma -- Long Lemma -- Linked Lemma -- Scope -- Commentary Styles -- Technical Vocabulary -- No Formula -- The Term פשר -- Syntactically Isolated פשרו -- פשרו על/ל -- פשרו אשר -- פשר הדבר -- פשר הפתגם -- Hermeneutical Techniques -- Citation of Works Other than the Base‑Text -- Exegetical Usage of Works Other than the Base‑Text -- Duplicate Commentary Manuscripts -- Psalms -- Isaiah -- Hosea -- Genesis 49 -- Number of Pesher Manuscripts in Comparison to Copies of the Base-Text -- Descriptive Typologies for Commentaries at Qumran -- Mesopotamian Commentary, Qumran Pesher: A Comparison of Formal Features -- Commentary in Mesopotamia -- Historical Origins -- Commentary Structures -- Physical Layout -- Tabular Layout -- Colon Layout -- Indent Layout -- Literary Structure -- Commentary Styles -- Technical Vocabulary -- Hermeneutical Techniques -- Borrowing Between Commentary Texts -- Duplicate Commentary Manuscripts.
Description based on publisher supplied metadata and other sources
Keywords: Jewish literature-History and criticism; Judaism-Relations-Assyro-Babylonian religion; Electronic books; Hochschulschrift